2015
DOI: 10.1111/codi.12932
|View full text |Cite
|
Sign up to set email alerts
|

Are bile acid malabsorption and bile acid diarrhoea important causes of loose stool complicating cancer therapy?

Abstract: BAM/BAD are very common and under-appreciated causes of GI symptoms after cancer treatment. Health professionals should have a low threshold in suspecting this condition, as diagnosis and treatment can significantly improve quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 22 publications
(28 reference statements)
0
30
0
Order By: Relevance
“…Another under-recognised group are those with cancer who have received pelvic chemoradiotherapy as >50% have bile acid diarrhoea. 128 …”
Section: Common Disodersmentioning
confidence: 99%
“…Another under-recognised group are those with cancer who have received pelvic chemoradiotherapy as >50% have bile acid diarrhoea. 128 …”
Section: Common Disodersmentioning
confidence: 99%
“…[40][41][42] Disrupted BA reabsorption in the ileum also precipitates BA malabsorption (BAM)/BA diarrhea (BAD), an under-appreciated and often mis-diagnosed condition in which reduced BA reabsorption-due to genetic mutations (type 2/primary BAM), ileal resection (type 1), or gastrointestinal disease (type 3)-results in abnormally high BA concentrations and water secretion in the colon. 43 Still, steady-state signaling through BA receptors is now recognized as essential for proper regulation of glucose and lipid metabolism, insulin sensitivity, as well as intestinal immunity. 23,29 Even extra-intestinal functions of BAs have begun to emerge, ranging from the ability of BAs to directly promote hematopoietic stem/progenitor cell (HSPC) expansion in the fetal liver, 44 to BAdependent signaling in the CNS that regulates neuroinflammation and neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that this policy yields an abnormal SeHCAT scan in approximately half of patients. 18,19 In addition, patients were asked to rate on a scale of 1-10 their quality of life at present (where 1 = very low and 10 = perfect) and the severity with which their bowel symptoms affect their quality of life (where 1 = not at all and 10 = all the time).…”
Section: Methodsmentioning
confidence: 99%
“…Primary BAD affects approximately 1% of the population. 10 Secondary BAM/BAD -described frequently after upper GI surgery, with pancreatic disease, during chemotherapy or biological therapies for cancer, during and after pelvic radiotherapy, after terminal ileal resection for Crohn's disease or cancer, in those with microscopic colitis and a number of other conditions [11][12][13][14][15][16][17][18][19][20] -affects unquantified, but substantial, numbers of patients. The failure to diagnose this condition -it is frequently misdiagnosed as irritable bowel syndrome -not only means that difficult symptoms are not treated optimally but also impacts on the health economy; many undiagnosed patients undergo, sometimes repeatedly, unnecessary and expensive tests (eg colonoscopy) and are offered ineffective and frequently costly medications.…”
Section: Introductionmentioning
confidence: 99%